2017
DOI: 10.1177/0269215517748454
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hydrokinesiotherapy on postural balance of hemiplegic patients after stroke: a systematic review and meta-analysis

Abstract: HT is superior to land therapy program regarding postural balance in terms of BBS, ML and AP sway velocity of center of pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
14
0
3
Order By: Relevance
“…It has also been noted that increased somatosensory inputs and visual deprivation might exert positive effects on top of balance training, as well as enriched environment 4,5,18,19 . Water-based exercise, by utilizing the properties of water, including buoyancy, viscosity, turbulence, and hydrostatic pressure, has been suggested to improve balance control 20,21 . Two reviews summarized that the water-based exercise for neurological disorder covers a wide variety, including resistance training, movement facilitation, motor control training, balance training, coordination training and other specific techniques 21,22 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been noted that increased somatosensory inputs and visual deprivation might exert positive effects on top of balance training, as well as enriched environment 4,5,18,19 . Water-based exercise, by utilizing the properties of water, including buoyancy, viscosity, turbulence, and hydrostatic pressure, has been suggested to improve balance control 20,21 . Two reviews summarized that the water-based exercise for neurological disorder covers a wide variety, including resistance training, movement facilitation, motor control training, balance training, coordination training and other specific techniques 21,22 .…”
mentioning
confidence: 99%
“…Two reviews summarized that the water-based exercise for neurological disorder covers a wide variety, including resistance training, movement facilitation, motor control training, balance training, coordination training and other specific techniques 21,22 . They indicated that stroke patients improved significantly more in weight shifting ability, dynamic balance, and functional mobility as compared with the land-based intervention 21,22 .Ai Chi, first developed by Jun Konno in 1990s 23 , is one kind of water-based exercise emphasizing characteristics of balance training 24 . It resembles Tai Chi on land, complemented by Zen shiatzu and Watsu concepts 25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tekrar sandalyeye oturdukları andaki skorları kronometre tutularak saniye cinsinden kaydedildi. TUG'da testin 10 saniyeden önce bitirilmesi fonksiyonel bağımsızlığı, 30 saniyeden uzun sürede bitirilmesi ise fonksiyonel bağımlılığı gösterir [30][31][32][33] .…”
Section: Ayak Plantar Yüzeyinin Duyu Eşiklerinin öLçümüunclassified
“…Одним из ярких примеров критики «статистического» подхода к интерпретации результатов является комментарий к метаанализу G. Iatridou и соавт. «The effectiveness of hydrokinesiotherapy on postural balance of hemiplegic patients after stroke: a systematic review and metaanalysis» [8], опубликованный M. Saltychev и соавт. [9] в феврале 2018 г. В данном комментарии авторы указывают, что при интерпретации данных метаанализа необходимо ориентироваться не на точечные оценки (средний эффект), а на доверительные интервалы для величины эффекта, и рассматривать нижнюю границу для доверительного интервала (минимальную эффективность) как величину, которая должна сопоставляться с оценкой клинической значимости.…”
Section: № 4 1st Editionunclassified